Comparison of unilateral biportal endoscopic lumbar fusion and modified minimally invasive tubular lumbar fusion for lumbar disc herniation: a two-year retrospective study - Qi, Jialong; Liu, Mingxiang; Shan, Tao; Dong, Zhou; Han, Guosong; Ni, Zhihao; Zheng, Ke; Ma, Li; Zhang, Zhidong (Frontiers in Neurology, 2025)
ObjectiveTo compare the medium- and long-term clinical outcomes of Unilateral Biportal Endoscopic Lumbar Fusion (UBE-TLIF) and Modified Minimally Invasive Tubular Lumbar Fusion (MIS-TLIF) for treating Lumbar Disc Herniation (LDH).MethodsA retrospective analysis was conducted on 86 patients with single-level LDH who underwent surgery between August 2022 and August 2023. Patients were allocated to two groups: 42 underwent UBE-TLIF and 44 underwent MIS-TLIF. We recorded operative time, postoperative drainage volume, and complication rates. Pain and functional recovery were assessed using the Visual Analogue Scale (VAS) for back and leg pain and the Oswestry Disability Index (ODI) preoperatively and at 3 days, 1, 6, 12, and 24 months postoperatively. Surgical outcomes were evaluated at 12 months using the MacNab criteria.ResultsThe mean operative time was significantly longer in the UBE-TLIF group than in the MIS-TLIF group (140.42 ± 16.02 min vs. 92.15 ± 13.14 min, p < 0.05). However, the UBE-TLIF group had a significantly lower postoperative drainage volume (65.79 ± 13.46 mL vs. 103.58 ± 12.56 mL, p < 0.05). Both groups showed significant improvements in VAS and ODI scores at all postoperative time points compared to preoperative baselines (p < 0.05). Although most intergroup differences in VAS and ODI scores were not statistically significant (p > 0.05), the UBE-TLIF group demonstrated lower scores across all follow-ups, with the difference at 3 days postoperatively being significant (p < 0.05). According to the MacNab criteria, the excellent-good rate was 95.2% for UBE-TLIF and 95.5% for MIS-TLIF, indicating no significant difference (p > 0.05). The fusion rates, assessed via the Bridwell grading system, were 90.4% (UBE-TLIF) and 93.2% (MIS-TLIF), which was also not a statistically significant difference (p > 0.05).ConclusionBoth UBE-TLIF and MIS-TLIF demonstrate comparable medium- and long-term clinical efficacy for LDH. UBE-TLIF is associated with less postoperative drainage and significantly better early pain relief, suggesting less soft tissue trauma. However, it was linked to a longer operative time in this study.